A Stepwise NaHSO3 Addition Mode Greatly Improves H2 Photoproduction in Chlamydomonas reinhardtii - Wei, Lanzhen; Li, Xin; Fan, Baoqiang; Ran, Zhaoxing; Ma, Weimin (Frontiers in Plant Science, 2018)
NaHSO3 addition greatly increases the yield of H2 photoproduction in a unicellular green alga Chlamydomonas reinhardtii through removing O2 and activating hydrogenase but significantly impairs the activity of PSII, an electron source for H2 photoproduction. Here, a stepwise addition mode of total 13 mM NaHSO3, an optimal concentration for H2 photoproduction of C. reinhardtii identified in a previous one step addition method, significantly improved H2 photoproduction. Such improvement was believed to be the result of increased residual PSII activity in an anaerobic background, but was at least independent of two alternative electron sinks for H2 photoproduction, cyclic electron transport around PSI and CO2 assimilation. Based on the above results, we propose that increased residual PSII activity in an anaerobic environment is an efficient strategy to enhance H2 photoproduction in C. reinhardtii, and the stepwise NaHSO3 addition mode is a case study in the strategy.